2009
DOI: 10.1111/j.1472-8206.2008.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal abnormalities during benzo(a)pyrene‐induced experimental lung carcinogenesis – defensive role of capsaicin

Abstract: The objective of the present study was to investigate whether lysosome is a target in benzo(a)pyrene-induced, oxidative stress-mediated lung cancer in Swiss albino mice and the plausible role of the phytochemical substance capsaicin in mitigating lysosomal damage. Oxidative stress was assessed based on the level of carbonyl content. The activities of lysosomal proteases like cathepsin-D, cathepsin-B, beta-D-glucosidase, beta-D-galactosidase, beta-D-glucuronidase, beta-D-N-acetylglucosaminidase and acid phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…DT‐diaphorase (DTD) is a flavoprotein that catalyzes the two electron reduction of quinones and other nitrogen oxides . This reaction prevents one electron redox cycling of these groups, thereby inhibiting the formation of DNA damaging ROS . In our present study, a substantial increase in lung phase I enzymes was observed in the carcinogen‐treated animals, which was reversed following BE treatment.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…DT‐diaphorase (DTD) is a flavoprotein that catalyzes the two electron reduction of quinones and other nitrogen oxides . This reaction prevents one electron redox cycling of these groups, thereby inhibiting the formation of DNA damaging ROS . In our present study, a substantial increase in lung phase I enzymes was observed in the carcinogen‐treated animals, which was reversed following BE treatment.…”
Section: Discussionmentioning
confidence: 50%
“…Electron microscopic analysis of B(a)P‐treated lung sections showed complete loss of architecture in lysosomes of cancer‐bearing animals indicating lysosomal damages. The defects in lysosomal architecture would lead to the alterations in the lysosomal metabolism, resulting in decreased activities of lysosomal enzymes in the B(a)P‐induced lung, thus becoming a key contributor to intrinsic cell dysfunction . The near‐normal appearance of the lung tissue on supplementation with BE shows the protective effect of BE in B(a)P‐induced disruption of lysosomal fine structure.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, capsaicin prevented pronounced oxidative damage caused by BP to biomolecules, preserved lysosomal stability, restored the activities of phase I and II biotransformation enzymes and the levels of tumor markers to near normalcy. BP-induced lung cancer animals showed abnormal changes in body weight, tumor incidence, low blood glucose and alterations in lipid levels, all of which were significantly reversed by capsaicin (Anandakumar et al 2008;Anandakumar et al 2008aAnandakumar et al , 2008bAnandakumar et al2009aAnandakumar et al , 2009b; Anandakumar, P., Kamaraj, S., Jagan, S., Ramakrishnan, G., Naveenkumar, et al 2009). …”
Section: Teel and Huynh 1999mentioning
confidence: 99%
“…twice weekly for 4 weeks increased lysosomal enzyme activities and oxidative stress, altered phase I and II enzymes, increased serum tumor markers, changed body weight, and tumor incidences Capsaicin (10 mg/kg, i.p.) 1 week prior to first BP dose for 14 weeks generally reversed all reported BP-induced changes, attenuated abnormalities and restored normal values Anandakumar et al 2008;Anandakumar et al 2008aAnandakumar et al , 2008bAnandakumar et al2009aAnandakumar et al , 2009b; Anandakumar, P., Kamaraj, S., Jagan, S., Ramakrishnan, G., Naveenkumar, et al 2009 B6 mice DMBA-initiated and TPA-promoted TRPV1 WT mice showed more tumors than KO mice DMBA-initiated mice showed no tumors with topical capsaicin applications Capsaicin co-administration enhanced TPA-promoted tumors Bode et al 2009;Hwang et al 2010 papillary or nodular hyperplasia of the urinary bladder. Incidences of carcinogen-induced lesions of the thyroid and kidney were not significantly altered by capsaicin.…”
Section: Teel and Huynh 1999mentioning
confidence: 99%
See 1 more Smart Citation